(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Tachyons are Scalar Bosons that reside in our fourth dimensional spatial Universe. They are point particles with zero mass, zero charge, and zero spin. Based on the Lorentz Transformation for v > c, tachyons can travel backwards in time to enter our third dimensional spatial Universe and can travel faster than light speed, to transmit information instantaneously between two entangled particles, to change their spin values from a superposition state to a definitive up and down state. We will show that the laws of Quantum Mechanics can be retro-causal while the laws of Classical Mechanics must be causal.